Small-x neutrino-hadron structure functions within the QCD color dipole picture - Gay Ducati, Maria Beatriz (2007)
We present an exploratory QCD analysis of the neutrino structure functions in charged current DIS using the color dipole formalism. The dipole cross sections are taken from recent phenomenological/theoretical studies in deep inelastic inclusive production. The theoretical predictions are compared to the available experimental results in the small-x region, which has never been considered so far.